Aqueous binders and slurries for nanocellulose-based secondary battery electrodes
A core-shell structured latex particle with nanocellulose forms strong hydrogen bonds to prevent particle migration in lithium secondary battery electrodes, ensuring uniform distribution and improved binding strength.
Patent Information
- Application Number
- JP2024541682
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-01-10
- Filing Date
- 2022-03-10
- Publication Date
- 2025-01-09
- Estimated Expiration
- 2042-03-10
AI Technical Summary
Conventional SBR water-based binders for lithium secondary battery electrodes experience a migration phenomenon where particles move to the upper layer during drying, reducing binding force.
A core-shell structured latex particle with a rubbery polymer core and a shell formed by a chemical reaction of monomers, combined with nanocellulose, forms strong hydrogen bonds to prevent particle migration and improve binding force.
The solution results in uniform binder distribution and enhanced electrode binding strength, with improved viscosity and stability of the slurry.
Smart Images

Figure 2025500666000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to nanocellulose-based aqueous binders and slurries for use in the manufacture of electrodes for lithium secondary batteries. [Background technology]
[0002] Electrodes for lithium secondary batteries are generally manufactured by applying a slurry containing an active material and a binder onto a metal current collector and drying it. The slurry for electrode preparation is obtained, for example, by mixing and kneading a negative electrode active material, a binder, and a dispersant. Slurries for use as aqueous binders consisting of styrene-butadiene rubber (SBR) and carboxymethyl cellulose (CMC) are known in the art. In the process of applying such conventional SBR aqueous binders to an electrode and drying it, there is a problem that the uniformly dispersed SBR particles migrate to the upper layer of the electrode together with the evaporated water (migration), which reduces the binding strength of the electrode. Therefore, research into new binder-related technologies that can suppress this migration phenomenon is required. Summary of the Invention [Problem to be solved by the invention]
[0003] The object of the present invention is to provide an aqueous binder and slurry for nanocellulose-based secondary battery electrodes, which contain latex particles with a core-shell structure and nanocellulose, thereby forming strong hydrogen bonds between the latex particles and nanocellulose, thereby suppressing the migration phenomenon of the SBR on the electrode layer that occurs in conventional technologies, and improving the binding strength of the electrode. [Means for solving the problem]
[0004] The aqueous binder for a nanocellulose-based secondary battery electrode according to one embodiment of the present invention can include core-shell structured latex particles including a core comprising a rubbery polymer; and a shell formed by chemical reaction of one or two monomers selected from the group consisting of acrylic monomers and non-acrylic monomers on the surface of the core; and nanocellulose interacting with functional groups on the surface of the shell.
[0005] The nanocellulose may be one or more selected from the group consisting of cellulose nanofibers (CNF), cellulose nanocrystals (CNC), and bacterial cellulose (BC).
[0006] Nanocellulose may be present in an amount of 0.01% to 1.0% by weight based on the total mass of the latex particle solids.
[0007] The chemical reaction that forms the shell may be a polymerization reaction.
[0008] The interaction may be a hydrogen bond.
[0009] The functional group on the shell surface may be one or more selected from the group including a carbonyl group, a carboxy group, and a nitrile group.
[0010] The rubber-like polymer may be one or more selected from the group consisting of butadiene rubber, acrylic rubber, ethylene-propylene copolymer rubber, styrene-butadiene copolymer rubber, acrylonitrile-butadiene copolymer rubber, isoprene rubber, ethylene-propylene-diene terpolymer rubber, polyorganosiloxane-polyalkyl(meth)acrylate rubber composite, and mixtures thereof.
[0011] The acrylic monomer may be one or more selected from the group consisting of methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, t-butyl (meth)acrylate, isobutyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, 2-ethylbutyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, cyclohexyl (meth)acrylate, n-octyl (meth)acrylate, isooctyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, dodecyl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, octadecyl (meth)acrylate, and isobornyl (meth)acrylate.
[0012] The non-acrylic monomer may be one or more selected from the group consisting of (meth)acrylamide, N-methyl(meth)acrylamide, N,N-dimethyl(meth)acrylamide, (meth)acrylonitrile, N-vinylpyrrolidone, N-vinylcaprolactam, N-vinylcaprolactone, styrene, 2-vinylpyridine, 4-vinylpyridine, and vinyl acetate.
[0013] A nanocellulose-based secondary battery electrode slurry according to one embodiment of the present invention may include the above-mentioned aqueous binder, negative electrode active material, and thickener.
[0014] The thickener may be one or more selected from the group consisting of cellulose-based polymers such as carboxymethylcellulose, methylcellulose, hydroxypropylcellulose, and the like, and their ammonium salts and alkali metal salts; (modified) poly(meth)acrylic acid, and the like, and their ammonium salts and alkali metal salts; (modified) polyvinyl alcohols such as copolymers of acrylic acid or acrylic acid salts with vinyl alcohol, and copolymers of maleic anhydride or maleic acid or fumaric acid with vinyl alcohol; polyethylene glycol; polyethylene oxide; modified polyacrylic acid; oxidized starch; starch phosphate; casein; and hydrogenated acrylonitrile-butadiene copolymers.
[0015] The secondary battery electrode according to an embodiment of the present invention may be manufactured using the above-mentioned slurry.
[0016] The secondary battery electrode according to one embodiment of the present invention may have a peel strength of 8.5 gf / cm or more before vacuum drying and a peel strength of 9.0 gf / cm or more after vacuum drying during the manufacturing process. Effect of the Invention
[0017] The nanocellulose-based aqueous binder for secondary battery electrodes according to one embodiment of the present invention inhibits the migration of the binder as the electrode dries, resulting in a uniform distribution of the binder in the electrode and excellent electrode binding strength.
[0018] In addition, the nanocellulose-based secondary battery electrode slurry according to one embodiment of the present invention has improved viscosity and excellent slurry stability. [Brief description of the drawings]
[0019] [Figure 1] 3 is a photograph showing the presence or absence of aggregation and the surface state of the binders produced in Comparative Example 3, Example 1, and Example 2 of the present invention, observed with the naked eye. [Diagram 2]1 is a graph showing the relationship between the shear deformation rate and the viscosity of slurries of Comparative Example 2 and Examples 1 to 3 of the present invention, on a logarithmic scale. [Diagram 3] 1 is a graph comparing the adhesive strength of the electrodes before and after vacuum drying in the manufacturing process of Comparative Example 2, Comparative Example 3, and Examples 1 to 3 of the present invention. [Figure 4] FIG. 1 is a schematic diagram of a SAICAS measurement method carried out in Experimental Example 5 of the present invention. [Diagram 5] 1 is a graph comparing the horizontal forces acting during SAICAS measurement at different cutting depths of composite layers produced using Comparative Example 2, Comparative Example 3, and Examples 1 to 3 of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0020] Terms such as first, second and third are used to describe various parts, components, regions, layers and / or sections, but are not limited thereto. These terms are used only to distinguish one part, component, region, layer or section from another part, component, region, layer or section. Thus, a first part, component, region, layer or section described below can be referred to as a second part, component, region, layer or section without departing from the scope of the present invention.
[0021] The terminology used herein is merely for the purpose of referring to specific embodiments and is not intended to limit the present invention. As used herein, the singular form includes the plural form unless the text clearly indicates otherwise. As used herein, the meaning of "comprises" is intended to embody certain properties, regions, integers, steps, operations, elements and / or components, and does not exclude the presence or addition of other properties, regions, integers, steps, operations, elements and / or components.
[0022] When an item is described as being "on" or "above" another item, it may be exactly on or above the other item, or it may have other items between them. In contrast, when an item is described as being "directly on" another item, there are no other items between them.
[0023] Unless otherwise specified, % means % by weight, and 1 ppm is 0.0001% by weight. Unless otherwise defined, all terms, including technical and scientific terms, used herein have the same meaning as commonly understood by those of ordinary skill in the art to which the present invention belongs. Terms defined in commonly used dictionaries are further interpreted to have a meaning consistent with the relevant technical literature and the presently disclosed content, and are not interpreted in an ideal or very formal sense unless defined.
[0024] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS The present invention will now be described in detail with reference to the accompanying drawings, in which: FIG. 1 is a block diagram of a semiconductor device according to an embodiment of the present invention;
[0025] [Nanocellulose-based aqueous binder for secondary battery electrodes]
[0026] The aqueous binder for nanocellulose-based secondary battery electrodes according to one embodiment of the present invention may include latex particles with a core-shell structure including a core containing a rubber-like polymer; and a shell formed by a chemical reaction of one or two monomers selected from the group consisting of acrylic monomers and non-acrylic monomers on the surface of the core; and nanocellulose interacting with the functional groups on the surface of the shell. Specifically, the shell may be formed by a polymerization reaction of one or two monomers selected from the group consisting of acrylic monomers and non-acrylic monomers on the surface of the core. Specifically, the shell may be formed by a polymerization reaction of an acrylic monomer and a non-acrylic monomer on the surface of the core. By including nanocellulose, the latex particles with a core-shell structure that can form strong hydrogen bonds with nanocellulose as described below are fixed by the nanocellulose, so that the migration of the latex particles with a core-shell structure to the upper layer of the electrode together with the moisture evaporated during the electrode manufacturing process can be suppressed. Therefore, the distribution of the binder in the electrode is maintained uniform even after a drying process during electrode manufacturing.
[0027] The nanocellulose may be one or more selected from the group consisting of cellulose nanofibers (CNF), cellulose nanocrystals (CNC) and bacterial cellulose (BC). Specifically, the nanocellulose may be cellulose nanocrystals (CNC).
[0028] The functional group on the shell surface may be one or more selected from the group including a carbonyl group, a carboxy group, and a nitrile group. Specifically, it may be one or two selected from the group including a carbonyl group and a nitrile group. By including the functional group on the shell surface, it is possible to form a strong hydrogen bond with the hydroxyl group (-OH) of the nanocellulose.
[0029] Nanocellulose may be 0.01% by weight to 1.0% by weight based on the total mass of the solid content of the latex particles. Specifically, it may be 0.05% by weight to 0.9% by weight, and more specifically, it may be 0.05% by weight to 0.8% by weight. If the amount of nanocellulose added is too small, the effect of improving the dispersibility of the binder, the effect of suppressing the migration phenomenon of the core-shell structured latex particles in the electrode manufacturing process, and the effect of improving the binding strength of the electrode manufactured using the same are not fully exhibited, and if the amount is too large, hydrogen bonds between the nanocellulose and between the nanocellulose and the core-shell structured latex particles inside the binder are significantly increased, and aggregation is formed, which may significantly reduce the dispersibility of the binder and the binding strength of the electrode manufactured using the same.
[0030] The rubbery polymer may be one or more selected from the group consisting of butadiene rubber, acrylic rubber, ethylene-propylene copolymer rubber, styrene-butadiene copolymer rubber, acrylonitrile-butadiene copolymer rubber, isoprene rubber, ethylene-propylene-diene terpolymer rubber, polyorganosiloxane-polyalkyl(meth)acrylate rubber composite, and mixtures thereof. Specifically, the rubbery polymer may be styrene-butadiene copolymer rubber.
[0031] The acrylic monomer may be one or more selected from the group consisting of methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, t-butyl (meth)acrylate, isobutyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, 2-ethylbutyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, cyclohexyl (meth)acrylate, n-octyl (meth)acrylate, isooctyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, dodecyl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, octadecyl (meth)acrylate, and isobornyl (meth)acrylate. Specifically, the acrylic monomer may be one or more selected from the group consisting of n-butyl (meth)acrylate, t-butyl (meth)acrylate, isobutyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate, more specifically, one or more selected from butyl (meth)acrylate and 2-ethylhexyl methacrylate, more specifically, butyl (meth)acrylate and 2-ethylhexyl methacrylate.
[0032] The non-acrylic monomer may be at least one selected from the group consisting of (meth)acrylamide, N-methyl(meth)acrylamide, N,N-dimethyl(meth)acrylamide, (meth)acrylonitrile, N-vinylpyrrolidone, N-vinylcaprolactam, N-vinylcaprolactone, styrene, 2-vinylpyridine, 4-vinylpyridine, and vinyl acetate. Specifically, the non-acrylic monomer may be (meth)acrylonitrile.
[0033] [Nanocellulose-based slurry for secondary battery electrodes]
[0034] The slurry for the nanocellulose-based secondary battery electrode according to an embodiment of the present invention can include the above-described aqueous binder for the nanocellulose-based secondary battery electrode, the negative electrode active material, and the thickener. By including the above-described aqueous binder for the nanocellulose-based secondary battery electrode in the slurry, the viscosity of the slurry is improved.
[0035] Regarding the nanocellulose-based aqueous binder, since it is the same as described above, repeated explanations are omitted. The amount of the nanocellulose-based aqueous binder added to the slurry production may be 1 to 5 parts by weight with respect to 100 parts by weight of the slurry solid content. Specifically, it may be 1 to 3 parts by weight with respect to 100 parts by weight of the slurry solid content.
[0036] The negative electrode active material may be one or more selected from the group consisting of carbon and graphite materials capable of insertion and deintercalation of lithium ions, Si-based materials, metals and compounds capable of alloying with lithium, composites of metals and their compounds with carbon and graphite materials, lithium-containing nitrides, and the like.
[0037] Examples of the carbon and graphite materials include natural graphite, artificial graphite, expanded graphite, carbon fiber, graphitization-resistant carbon, carbon black, carbon nanotube, fullerene, activated carbon, hard carbon, and soft carbon.
[0038] Examples of the Si-based materials include Si, SiOx (0 < x < 2), Si-Y alloy (where Y is an alkali metal, alkaline earth metal, group 13 element, group 14 element, transition metal, rare earth element, or a combination thereof), Si-C composite, or a Si-based compound of these combinations.
[0039] Examples of the metals and elements capable of alloying with lithium include Al, Si, Sn, Ag, Bi, Mg, Zn, In, Ge, Pb, Pd, Pt, Ti, etc. Specifically, the negative electrode active material may be a carbon and graphite material.
[0040] The amount of the negative electrode active material added to the slurry preparation may be 95 to 99 parts by weight based on 100 parts by weight of the slurry.
[0041] The thickener may be one or more selected from the group consisting of cellulose-based polymers such as carboxymethylcellulose, methylcellulose, and hydroxypropylcellulose, and their ammonium salts and alkali metal salts; (modified) poly(meth)acrylic acid, and their ammonium salts and alkali metal salts; (modified) polyvinyl alcohols such as copolymers of acrylic acid or acrylic acid salts and vinyl alcohol, copolymers of maleic anhydride or maleic acid or fumaric acid and vinyl alcohol; polyethylene glycol; polyethylene oxide; modified polyacrylic acid; oxidized starch; starch phosphate; casein; and hydrogenated acrylonitrile-butadiene copolymers. Specifically, the thickener may be carboxymethylcellulose.
[0042] If the viscosity of the slurry is too low, layer separation occurs, whereas if the viscosity of the slurry is too high, uniform electrode application is not possible. Therefore, by adding a thickener to the slurry, the viscosity of the slurry can be adjusted to an appropriate level, thereby imparting electrode application properties.
[0043] The amount of thickener added to the slurry preparation may be 0.5 to 1.5 parts by weight per 100 parts by weight of the slurry.
[0044] The slurry according to an embodiment of the present invention may further include a solvent as necessary, such as, but not limited to, N-methylpyrrolidone, acetone, or water, and any solvent available in the art may be used.
[0045] [Secondary battery electrode]
[0046] The secondary battery electrode according to one embodiment of the present invention may be prepared using the above-mentioned slurry. The slurry is the same as described above, so repeated explanations will be omitted. By using the above-mentioned slurry, a secondary battery electrode with excellent binding strength can be prepared.
[0047] The secondary battery electrode may be a negative electrode. The negative electrode may be prepared by applying a negative electrode slurry of a mixture of distilled water, a negative electrode active material, carboxymethyl cellulose, and the nanocellulose-based aqueous binder for secondary battery electrodes onto a conductive negative electrode current collector using an applicator, a doctor blade, immersion, brush coating, or the like, and then vacuum drying at 80°C to 150°C for 5 minutes to 60 minutes. The thickness of the negative electrode after vacuum drying may be 20 μm to 150 μm.
[0048] The current collector is a portion where the transfer of electrons occurs due to the electrochemical reaction of the active material. The negative electrode current collector can be manufactured to a thickness of 5 μm to 30 μm. The negative electrode current collector is not particularly limited as long as it does not induce a chemical change in the battery and has electrical conductivity, and for example, copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, a polymer substrate coated with a conductive metal, or a combination thereof can be used.
[0049] The secondary battery electrode may have a peel strength of 8.5 gf / cm or more before vacuum drying and a peel strength of 9.0 gf / cm or more after vacuum drying during the manufacturing process. EXAMPLES
[0050] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS The present invention will now be described in detail with reference to the accompanying drawings, in which: FIG. 1 is a schematic diagram of a method for manufacturing a semiconductor device according to the present invention;
[0051] [Comparative Example 1] (1) Binder preparation Using a high-pressure reactor, 140 parts by weight of distilled water was emulsified by adding 1-0.5 parts by weight of sodium dodecylbenzenesulfonate as an anionic surfactant, 3 parts by weight of a mixture of 1,3-butadiene and styrene in a 4:6 ratio as an SBR seed, and 1-3 parts by weight of itaconic acid. An additional 100 parts by weight of the mixture of 1,3-butadiene and styrene in a 4:6 ratio was added and emulsified by stirring, and then 0.3 parts by weight of potassium sulfate as a decomposition initiator was added to carry out an emulsion polymerization reaction to prepare an SBR binder.
[0052] (2) Slurry and electrode preparation Based on a total of 100 parts by weight of slurry solids, 97.4 parts by weight of graphite as an active material, 1.5 parts by weight of the binder particles obtained above, and 1.1 parts by weight of carboxymethyl cellulose were mixed, and distilled water was added thereto to adjust the solid content of the slurry to 20% by weight to 80% by weight. The mixture was then uniformly applied to a Cu thin film having a thickness of 10 μm using an applicator, dried, and rolled using a roll press to prepare a negative electrode.
[0053] [Comparative Example 2] An SBR binder was prepared in the same manner as in Comparative Example 1, and after 4 hours, 4 parts by weight of an acrylic monomer (0.6 parts by weight of butyl (meth)acrylate, 0.2 parts by weight of acrylonitrile, and 3.2 parts by weight of 2-ethylhexyl methacrylate) and 0.2 parts by weight of a decomposition initiator potassium sulfate were added to 1 part by weight of the SBR binder to carry out an emulsion polymerization reaction, thereby polymerizing a binder with a core-shell structure of SBR-Acryl. Using the obtained binder, a slurry and an electrode were prepared in the same manner as in Comparative Example 1.
[0054] [Comparative Example 3] A binder was prepared by adding 5% by weight of nanocellulose (CNC) based on the solid content of SBR-Acryl to a core-shell structured binder of SBR-Acryl prepared in the same manner as in Comparative Example 2. Using the obtained binder, a slurry and an electrode were prepared in the same manner as in Comparative Example 1.
[0055] [Example 1] A binder was prepared by adding 0.1% by weight of nanocellulose (CNC) based on the solid content of SBR-Acryl to a core-shell structured binder of SBR-Acryl prepared in the same manner as in Comparative Example 2. Using the obtained binder, a slurry and an electrode were prepared in the same manner as in Comparative Example 1.
[0056] [Example 2] A binder was prepared by adding 0.5% by weight of nanocellulose (CNC) based on the solid content of SBR-Acryl to a core-shell structured binder of SBR-Acryl prepared in the same manner as in Comparative Example 2. Using the obtained binder, a slurry and an electrode were prepared in the same manner as in Comparative Example 1.
[0057] [Example 3] A binder was prepared by adding 0.75% by weight of nanocellulose (CNC) based on the solid content of SBR-Acryl to a core-shell structured binder of SBR-Acryl prepared in the same manner as in Comparative Example 2. Using the obtained binder, a slurry and an electrode were prepared in the same manner as in Comparative Example 1.
[0058] [Experimental Example 1] The presence or absence of aggregation and the surface state of the binders prepared in Comparative Example 3, Example 1, and Example 2 were observed with the naked eye and are shown in Figure 1. It can be seen that the binders of Example 1 and Example 2 have smooth surfaces, but the binder of Comparative Example 3 has many curves on the surface due to internal aggregation. This is because the amount of nanocellulose (CNC) added was excessive relative to the SBR-Acryl solid content, which significantly increased the number of hydrogen bonds between nanocellulose inside the binder and between nanocellulose and the carbonyl or nitrile groups of the SBR-Acryl binder, resulting in aggregation.
[0059] [Experimental Example 2] The binders prepared in Comparative Example 1, Comparative Example 2, and Example 1 were mixed with distilled water to prepare binder suspension compositions containing 0.05 to 0.1 wt % of binder solid content. The zeta potential of the binder suspension compositions was measured at room temperature, and the results are shown in Table 1 below.
[0060] Zeta potential is generally measured by measuring the surface potential of the electric double layer that particles have. When the zeta potential value is ±30mV to ±60mV (absolute value is 30 to 60mV), the dispersibility is judged to be stable, and the larger the absolute value, the higher the surface potential value, and therefore the more stable it can be judged to be.
[0061] [Table 1]
[0062] Referring to Table 1, the absolute value of the zeta potential in Comparative Example 2 is greater than that in Comparative Example 1, so it can be seen that the dispersibility of the binder is improved by forming an SBR-Acrylic core-shell structure, but in the case of Comparative Example 3 in which an excessive amount of nanocellulose (CNC) is added, it can be seen that a large amount of aggregation occurs inside the binder, causing a significant decrease in dispersibility, as confirmed by the naked eye in Experimental Example 1. Through Examples 1 to 3, which show a much higher absolute value of the zeta potential than Comparative Example 2, which has relatively stable dispersibility, it can be seen that when an appropriate amount of nanocellulose (CNC) is added to a binder with an SBR-Acrylic core-shell structure, the dispersibility of the binder is further improved.
[0063] [Experimental Example 3] 2 is a graph showing the relationship between the shear deformation rate and the viscosity of the slurries of Comparative Example 2 and Examples 1 to 3 on a logarithmic scale. Referring to this, it can be seen that the viscosities of the slurries of Examples 1 to 3, which were prepared by adding an appropriate amount of nanocellulose (CNC) to the binder of the SBR-Acryl core-shell structure, were increased compared to the slurry of Comparative Example 2. This is because the viscosity of the slurry was improved due to the formation of hydrogen bonds between the binder of the SBR-Acryl core-shell structure and the nanocellulose (CNC), which indicates that the stability of the slurry was increased and that the increased viscosity enabled more uniform application.
[0064] [Experimental Example 4] The electrodes prepared in Comparative Example 2, Comparative Example 3, and Examples 1 to 3 were cut to a size of 25 mm wide and 100 mm long. A double-sided tape of 20 mm wide and 40 mm long was attached to an acryl plate of 40 mm wide and 100 mm long. The prepared electrode was attached onto the double-sided tape, and then pressed lightly five times with a hand roller, and this was mounted on a UTM (20 kgf Load Cell) to peel off about 25 mm of one side of the negative electrode. The electrode was fixed to the upper clip of a tensile strength meter, and the tape attached to one side of the electrode was fixed to the lower clip, and the 180° peel strength was measured while peeling at a speed of 100 mm / min, as shown in FIG. 3. Five or more specimens were prepared for each sample, and the values of the electrodes before and after vacuum drying (before VD (Vacuum Dry)) were measured, and the average value was calculated. Vacuum drying was performed at 110°C for 4 hours. The results of Figure 3 are summarized in Table 2 below.
[0065] [Table 2]
[0066] From the results in Table 2, it can be seen that when nanocellulose (CNC) is added to the SBR-Acryl core-shell structured binder in the amount proposed in the present invention, the electrode binding strength of the binder is improved compared to when no nanocellulose (CNC) is added, while when an excess of nanocellulose (CNC) is added, the electrode binding strength of the binder is decreased compared to when no nanocellulose (CNC) is added.
[0067] [Experimental Example 5] The binder dispersibility was compared for Comparative Example 2, Comparative Example 3, and Examples 1 to 3 using SAICAS (Surface and Interfacial cutting analysis system). Specifically, the appropriate amount of the slurry of Comparative Example 2, Comparative Example 3, and Examples 1 to 3 was uniformly applied on a 10 μm Cu thin film, and then dried to form a composite layer of 1 to 1000 μm, and the adhesive properties were analyzed while cutting and peeling the composite layer. The composite layer was cut to a specific depth with a micro-blade, and the horizontal force acting while peeling at a constant speed in a direction parallel to the interface between the Cu thin film and the composite layer was converted into adhesive force, and this process was simply illustrated and shown in FIG. 4. At this time, the composite layer was cut to a depth of 30%, 60%, and 90% from the upper surface of the composite layer, and each horizontal force was measured while peeling in the horizontal direction, and shown in FIG. 5, which are summarized in Table 3 below. This allows the dispersibility of the binder to be inferred.
[0068] [Table 3] (Unit: kN / m)
[0069] As can be seen from Table 3, Examples 1 to 3 have small deviations in the force acting in the horizontal direction regardless of the cutting depth, unlike Comparative Examples 2 and 3, and it can be confirmed that the binder dispersion is excellent. This is because, by adding nanocellulose (CNC) in the amount proposed in the present invention to the SBR-Acryl core-shell structured binder, strong hydrogen bonds are formed between the binder and nanocellulose (CNC) in the slurry, and migration of the binder is suppressed when the electrode is dried, so that the binder is maintained in a uniformly distributed state throughout the composite layer even after the electrode is dried, just as it was before the electrode was dried.
[0070] The present invention is not limited to the examples, and can be manufactured in various different forms, and a person having ordinary skill in the art to which the present invention pertains can understand that the present invention can be embodied in other specific forms without changing the technical idea or essential characteristics of the present invention. Therefore, it should be understood that the above-described examples are illustrative in all respects and not limiting.
Claims
1. A core comprising a rubbery polymer; and a shell formed by bonding one or two monomers selected from the group consisting of acrylic monomers and non-acrylic monomers to the surface of the core through a chemical reaction; Core-shell structured latex particles comprising: nanocellulose that interacts with functional groups on the shell surface; and an aqueous binder for a nanocellulose-based secondary battery electrode.
2. The nanocellulose is at least one selected from the group consisting of cellulose nanofibers (CNF), cellulose nanocrystals (CNC) and bacterial cellulose (BC). The aqueous binder for nanocellulose-based secondary battery electrodes according to claim 1.
3. The aqueous binder for nanocellulose-based secondary battery electrodes according to claim 1, wherein the nanocellulose is 0.01% by weight to 1.0% by weight based on the total mass of the latex particle solids.
4. The aqueous binder for nanocellulose-based secondary battery electrodes according to claim 1 , wherein the chemical reaction is a polymerization reaction.
5. 2. The nanocellulose-based aqueous binder for secondary battery electrodes according to claim 1, wherein the interaction is a hydrogen bond.
6. The aqueous binder for nanocellulose-based secondary battery electrodes according to claim 1, wherein the functional group on the shell surface is one or more selected from the group consisting of a carbonyl group, a carboxyl group, and a nitrile group.
7. The rubber-like polymer is at least one selected from the group consisting of butadiene rubber, acrylic rubber, ethylene-propylene copolymer rubber, styrene-butadiene copolymer rubber, acrylonitrile-butadiene copolymer rubber, isoprene rubber, ethylene-propylene-diene ternary copolymer rubber, polyorganosiloxane-polyalkyl (meth)acrylate rubber composite, and mixtures thereof. The aqueous binder for nanocellulose-based secondary battery electrodes according to claim 1.
8. The acrylic monomer is methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, t-butyl (meth)acrylate, isobutyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, 2-ethylbutyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, cyclohexyl (meth)acrylate, n-octyl (meth)acrylate, isooctyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, dodecyl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, octadecyl (meth)acrylate and isobornyl (meth)acrylate. The aqueous binder for nanocellulose-based secondary battery electrodes according to claim 1, which is at least one selected from the group consisting of acrylate.
9. The non-acrylic monomer is at least one selected from the group consisting of (meth)acrylamide, N-methyl(meth)acrylamide, N,N-dimethyl(meth)acrylamide, (meth)acrylonitrile, N-vinylpyrrolidone, N-vinylcaprolactam, N-vinylcaprolactone, styrene, 2-vinylpyridine, 4-vinylpyridine and vinyl acetate. The aqueous binder for nanocellulose-based secondary battery electrodes according to claim 1.
10. A nanocellulose-based secondary battery electrode slurry comprising the aqueous binder according to any one of claims 1 to 9, a negative electrode active material, and a thickener.
11. The thickener is a cellulose-based polymer such as carboxymethyl cellulose, methyl cellulose, hydroxypropyl cellulose, and their ammonium salts and alkali metal salts; (modified) poly(meth)acrylic acid, and their ammonium salts and alkali metal salts; (modified) polyvinyl alcohols such as acrylic acid or acrylic acid salts and vinyl alcohol copolymers, maleic anhydride or maleic acid or fumaric acid and vinyl alcohol copolymers; polyethylene glycol; polyethylene oxide; modified polyacrylic acid; oxidized starch; starch phosphate; casein; and acrylonitrile-butadiene copolymer hydrogenated product; The nanocellulose-based secondary battery electrode slurry according to claim 10, which is at least one selected from the group consisting of.
12. A secondary battery electrode produced using the slurry according to claim 11.
13. The secondary battery electrode according to claim 12 , wherein the peel strength before vacuum drying during the manufacturing process is 8.5 gf / cm or more and the peel strength after vacuum drying is 9.0 gf / cm or more.
Citation Information
Patent Citations
Binder composition for electrode, paint composition for electrode, electrode for power storage device, and power storage device
JP2020177849A
Slurry composition for lithium-ion secondary battery negative electrode, method for manufacturing lithium-ion secondary battery negative electrode, and lithium-ion secondary battery
JP6358256B2
Cited By
Electrode binder, electrode composition, and electrode
JP7854558B1